Could hyperthermia with proton therapy mimic carbon ion therapy? Exploring a thermo-radiobiological rationale. (November 2014) - Datta, Niloy R.; Puric, Emsad; Schneider, Ralf; Weber, Damien C.; Rogers, Susanne; Bodis, Stephan
Abstract Hyperthermia has been conventionally used in conjunction with photon beam irradiation. With a gradual increase in particle therapy facilities worldwide, this paper explores the physical, thermal and radiobiological implications of using a combination of hyperthermia with proton beam therapy. Hyperthermia is known to exhibit radiobiological features similar to those of high linear energy transfer radiation. Protons have many of the physical dose distribution properties of 12C ion therapy. Thus, the thermo-radiobiological advantages of hyperthermia coupled with the physical dose distribution advantages of proton beams could possibly mimic 12C ion therapy.